Aktivitas Protease, Amilase dan Lipase Digesti Ikan Medaka (Oryzias javanicus) yang Tertangkap di Segara Anakan Cilacap - Hana Hana; Untung Susilo; Sri Sukmaningrum (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2021)
Medaka fish (Oryzias javanicus) originating from Segara Anakan, Cilacap Regency has the potential as a bio-indicator of brackish water. The study of the physiological character of this species has not been done before, so that there needs to be basic information for domestication. The purpose of this study was to determine changes in protease, amylase and lipase digestive activity of medaka fish from Segara Anakan at different body sizes and salinity. The study was conducted by survey method. A sample of 567 medaka fish taken from three locations with different salinities (10 ± 1, 15 ± 1 and 20 ± 1 ppt) at the time of sampling, were used in this study. Medaka fish is grouped into three different sizes, namely (1) 0.063±0.01g (small), (2) 0.153±0.03 g (medium), and (3) 0.287±0.03 g (large). Measurements of enzyme activity were carried out by spectrophotometric methods. The results showed that body size and salinity were significantly different (P<0.05) on protease, amylase and lipase digestive activity of medaka fish. Large medaka fish shows higher digestive enzyme activity compared to the small body size in each salinity. However, amylase and lipase show same activity between different body sizes at 15±1 ppt. The higher the salinity, the lower the activity of protease, amylase and lipase. However, the salinity of 10±1-20±1 ppt shows the same amylase activity (small and medium size) and lipase (small size). Conclusion from the results of this study is the protease, amylase and lipase digestive activity of medaka fish that originating from Segara Anakan, Cilacap has been increased with increasing body size and decreasing environmental salinity. The results of this study are expected to contribute to the enrichment of fish biology, especially medaka fish.